EFL Students’ Coping Strategies for Speaking Anxiety During Online Learning - Nabilah Nurfajri Maharani; Roslaini Roslaini (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
The anxiety of learning a foreign language can be an obstacle in achieving the learning goals. Concerning the learning anxiety, the students of the English Education Study Program of FKIP UHAMKA were also dealing with the anxious experience when learning speaking conducted online. It seems unavoidable for students of English Foreign Language (EFL) to face anxiety when online learning. For this reason, the purpose of this study is to investigate the coping strategies that most students use to overcome speaking anxiety during online learning. 62 students in the fourth semester were respondents to this study. The data were then qualitatively collected using two types of questionnaires: closed-ended and open-ended questionnaires. The collected data were analyzed using descriptive analysis, which described and tabulated the students’ responses. After analyzing the closed-ended and open-ended responses, it is reasonable to conclude that the respondents mostly used the strategies of preparation, positive thinking, and peer seeking to cope with speaking anxiety in the context of online learning. In addition, based on open-ended responses, preparation was the most commonly used strategy by them.